Aksillere temperatuur vergelyk met timpaniese membraan temperatuur in kinders - G Greyling; MJ Viljoen; G Joubert (AOSIS, 2000)
The purpose of the study was to measure the axillary temperature at three, six and nine minutes in a hundred children between the ages of one and twelve years who were selected in a non-random deliberate way, and to compare the measurements with the tympanic membrane temperature (golden standard) which was measured in the test persons at the same time. The results were described by sensitivity, specificity, limits of agreement, and predictive values. From some of the findings of the research it is apparent that the axillary temperature reading increased after measurement of three, six and nine minutes. A maximum temperature reading was reached after three minutes in only 9% of the test persons, in 25% after six minutes and in 66% after nine minutes. From the findings it is clear that the ranges that were used influenced the sensitivity of the measurements, and it would appear that the range 35,5°C to 37,2°C was the best range to measure pyrexia in the age group one to 12 years. The 9- minute measurement then had the highest sensitivity. However, the specificity of measurement in this range was lower. The conclusion was drawn that axillary temperature measurement is an acceptable method, with certain reservations, to use as screening method for pyrexia in emergency divisions or clinics.